Bridging the Gap in Employee Zakat Deductions: A Fiqh-Based Examination of Corporate Zakat Practices in Medan, Indonesia - Ahmad Mafaid; Jhon Tyson Pelawi (Hukum Keluarga Islam IAIN LANGSA, 2025)
This study aims to analyze the obligation of employee zakat, which is directly deducted by companies, based on the provisions of the Fiqh of Corporate Zakat as formulated by BAZNAS and PERBAZNAS. The study focuses on the inconsistency of the liability principle in calculating corporate zakat, which is typically based on net assets, compared to the practice of employee zakat, which is often deducted from gross income without considering the employee's personal zakat obligations. This research adopts a qualitative approach with a case study design, examining several companies in the Medan area, including BRI, BNI, Bank Sumut Syariah, and BMI. Data were collected through in-depth interviews, document analysis, and non-participatory observations and were analyzed using the interactive model developed by Miles and Huberman. The results show that most of the companies studied (BRI, BNI, and Bank Sumut) failed to apply the liability reduction principle in employee zakat deductions as required. In contrast, one company (BMI) adhered to the liability principle in its employee zakat deductions, as outlined in corporate zakat guidelines. These findings highlight regulatory gaps and injustices in the treatment of employee zakat and emphasize the need for harmonizing Fiqh principles, technical policies, and field practices to create a fairer zakat system in accordance with the Maqasid Sharia